1998
DOI: 10.1209/epl/i1998-00295-7
|View full text |Cite
|
Sign up to set email alerts
|

New chains of boron and boron hydrogen

Abstract: Ab initio quantum chemical methods were used to study ground-state energies and geometrical configurations of boron and boron hydrogen chains. The ground-state energies of the boron chain were found to be comparable with those of boron clusters. The structure of chains can be obtained by unfolding the two rings of boron nanotubes. The ab initio ground-state energies of the dimerized (BH)n chain were fitted into the SSH model, in order to determine the corresponding parameters for the ground-state energy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…However, because of the proximity of the structures' energy to that of the true ground-state geometries, they can be regarded as metastable states. 28 Thus, with some experimental manipulation, it may be possible to realize such structures in laboratory. Keeping this possibility in mind, we decided to compute the static polarizabilities of ladderlike quasi-one-dimensional structures of boron by ab initio manybody methods.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, because of the proximity of the structures' energy to that of the true ground-state geometries, they can be regarded as metastable states. 28 Thus, with some experimental manipulation, it may be possible to realize such structures in laboratory. Keeping this possibility in mind, we decided to compute the static polarizabilities of ladderlike quasi-one-dimensional structures of boron by ab initio manybody methods.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have also reported theoretical calculations on the boron clusters. 17,18,19,20,21,22,23,24,25,26,27,28,29,30 Boustani et al 21 have shown theoretically that, similar to carbon, boron has a strong potential to form stable nanotubular structures. Boustani and coworkers recently studied small cationic 22 and neutral boron clusters 23 and obtained structures that are fundamentally different from crystal subunits of the well-known α− and β− rhombohedral phases of boron, which consist mainly of B 12 icosahedra.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the convex and spherical clusters are basically composed of a combination of pentagonal (at least one) and hexagonal pyramids (6,12), and the study of the fusion of two and three B icosahedral units suggests that closed tubular structures could be formed inside hypothetical -boron quasicrystals (13,14). Besides composite boron structures doped with foreign atoms [15], boron and boron}carbon chains as well as boron}hydrogen and boron}carbon}hydrogen chains have been investigated (16,17). Due to the fact that one of the most important problems in the "eld of quasicrystals is the determination of the atomic positions, we begin our considerations by studying the rhombohedral unit cells of real -boron crystals.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental activities in building and investigating boron nanostructures have been accompanied by theoretical activities. The electron deficient character of boron leads to high structural flexibility, and in fact, ab initio calculations predict a variety of boron structures to be stable, including layered, tubular and chain-like boron structures [15][16][17][18]. The BNWs that we observed on Mo(110) are 2-10 nm wide and up to 1 lm long (Fig.…”
mentioning
confidence: 89%